Development of a Driving School Simulation: Driving Success - ABDUL HALIM, MUHAMMAD SHAHRUL IKHWAN; Mohd Farhan , Mohd Farhan (Applied Information Technology And Computer Science, 2026)
Education is a very important subject and can be delivered well through the right methods. This study examines the difficulties associated with the conventional physical driving school system in Malaysia, especially focusing on the high expenses associated with vehicle maintenance. Driving learning centers suffer from a shortage of circuits which affects students’ learning sessions. Therefore, the main objective is to design a virtual driving school simulation application for driving school students that focuses on theory and circuit tests, featuring modules specifically designed to align with Malaysian standards, focusing on individuals preparing to take the driving license examination. The application was developed using Agile methodology, integrating Virtual Reality (VR) to create an immersive experience. Virtual driving school simulation using VR technology and appropriate hardware has the potential to increase accessibility and improve user learning outcomes. Future work can expand the scope of the application to include mobile platforms and involve advanced technologies for personalized training and feedback. The project demonstrated excellent usability and high user satisfaction through calculating an average System Usability Scale (SUS) score of 85.50 percent from respondent user acceptance score.